PRODUKSI ENZIM INULINASE Pichia manshurica DUCC-Y015 DENGAN PENAMBAHAN SUBSTRAT TEPUNG BENGKOANG (Paschyrhizus erosus) - Adzar Rofiqoh; W Wijanarka; Susiana Purwantisari (Jurnal Akademika Biologi, 2017)
Bengkoang (Pachyrhizus erosus) tubers has a high inulin content. Inulin bengkoang flour can be used as substrate to produce inulinase enzyme. The inulinase enzyme can be produced by Pichia manshurica DUCC-Y015. This research aims to determine the ability of Pichia mansurica DUCC-Y015 in producing inulinase enzyme with the addition of several variations of substrate concentration of bengkoang flour in its production medium. Determination of inulinase activity was done by DNS method. This research used a Completely Randomized Design (RAL) with 4 treatments: B0 (control), B1 (1 g bengkoang flour), B2 (3 g bengkoang flour) and B3 (5 g bengkoang flour). Each treatment was repeated 3 times. The inulinase activity of each treatment was 0.029 IU/mL, 0.033 IU/mL, 0.053 IU/mL and 0.015 IU/mL. The addition of variation substrate concentration bengkoang flour in the production medium did not affect the inulinase activity of Pichia manshurica DUCC-Y015Kata Kunci: Pachyrhizus erosus, inulinase, Pichia manshurica DUCC-Y015.